DETERMINANTS OF COVID-19 PREVENTION BEHAVIOR IN WOMEN OF REPRODUCTIVE AGE IN SOUTH TANGERANG CITY YEAR 2020 - Violita Agnoviardi; Mizna Sabilla; Luqman Efendi; Istianah Surury (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Coronaviruses, which are responsible for diseases in humans and animals, including Middle East Respiratory Syndrome (MERS), Severe Acute Respiratory Syndrome (SARS), and COVID-19, are a group of viruses known to cause respiratory infections in humans. Monitoring data for COVID-19 in South Tangerang City until February 2 2023 states that South Tangerang City is in the first level with the highest cases in Banten Province with 117,671 positive confirmed cases. This study aims to determine the determinants associated with COVID-19 prevention behavior in Women of Reproductive Age. This research was conducted in January 2023 using a cross-sectional design. The research sample was taken using the One-Stage Cluster and found as many as 190 women aged between 15-49 years. The results showed that most of the behaviors for preventing COVID-19 were good, most were aged <25 years (63.7%), had secondary education (58.9%), working status (60%), good knowledge (95, 3%) and good attitude (52.1%). In the variables of age, education, work, and knowledge, the results obtained were p value > 0.05. Meanwhile, the attitude variable obtained a p-value <0.05. Age, education, occupation, and knowledge are not related to COVID-19 prevention and only attitude factors are related to COVID-19 prevention behavior. It is recommended for the community to improve good attitudes to produce good COVID-19 prevention behavior.